Rural Health Care Workers and Local Residents Health Status in Yulong County of Yunnan Province China and Hat Yai City of Songkhla Mansion Thailand - Qu Fanwei; Jiang Yanling; Virasakdi Chongsuvivatwong; Tippawan Liabsuetrakul; Li Yan; Cai Le; Jiang Runsheng (Journal of Nepal Medical Association, 2017)
Introduction: To compare health status between Hat Yai city of Songkhla Province in Thailand and Yulong county of Yunnan province in China about rural health care workers and local residents, analyzing of both differences, learning from the advanced experience and practice of Thailand, adjusting policy, especially for the implementation of measures to improve the lack of human resources construction of Yulong County rural health, promote the level of rural health service of Lijiang. Methods: A qualitative study consisting of focus group discussions and individual in-depth interviews were conducted in Rural Health Care Workers and Local Residents Health Status in Yulong County of Yunnan Province China and Hat Yai City of Songkhla Mansion Thailand from. Results: Compared to 41(100%) bachelor's degree of medical staffs in Hat Yai, this accounted only 94 (42%) bachelor's degree of medical staffs in Yulong county hospital, and 31 (12%)in townships hospitals. For medical workers in Hat Yai, they have at least one time on-job training per year, but for Yulong county, only 144 (29%)of the medical personnel participated in the training per year. Health expenditures of Yulong county was mainly borne by the local government, and medical insurance coverage rate is 217,107 (99%). Insurance average awareness of Hat Yai is 4449 (66.4%), Yulong County is 62,501 (28.5%), P<0.001, there are statistically significant differences between two cities. Conclusions: Thailand has good experience in training, well-paid, motivating and retaining talent for rural health human resources; multi-pronged, mechanism innovation, establish and perfect the system of human resources for health, is the essential way to solve the problem. Keywords:  Hat Yai city; Yulong County; Rural medical staff; Variance analysis.